Efecto de la inversión extranjera directa en la contaminación ambiental para 18 países de América Latina durante el periodo de 1990-2018 - Ojeda Yaguana, Thalía Silvana (2020)
Foreign direct investment from Latin America has been increasing in recent years, rising from $95.735 billion in 1990 to $84.287 billion in 2019 (ECLAC, 2020). This growing trend has contributed to a higher level of environmental pollution, mainly due to the accelerated increase in human activity, exploitation of natural resources, and weak environmental regulation by governments. Therefore, the objective of this research is to analyze the effect of FDI on environmental pollution in Latin America during the period 1990-2018. Data from the World Bank (2019) and the Emissions Database for Global Atmospheric Research (EDGAR, 2019) were used to carry out this research. Using as dependent and independent variables CO2 emissions and FDI respectively, and the control variables: GDP and population. The methodology used comprises a GLS model that determines the relationship of the variables; two tests of cointegration to identify whether there is long-term equilibrium and a test of causality. The results indicate a significant positive relationship between environmental pollution and FDI, as well as a positive relationship between control variables and pollution. Likewise, it is confirmed that there is a long-term equilibrium relationship and the existence of two-way causality is verified. Based on these results, it is suggested that governments should establish stricter environmental standards, incentives, or introduction of FDI that produces with clean technologies, which will not only help maintain a cleaner environment but also greater technical and scientific development.